Effects of slope position and sampling time on soil fauna diversity indices under coconut cultivation planted in a low slope gradient area: a short-term study - Khairun Nisa Kamarudin,; Mohammad Aizad Mohamad Sulaimin,; Maulana Insanul Kamil,; Irwin Mirza Umami, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A short-term studies of soil fauna on the low slope gradient under coconut plantation is not well explored due to tedious and time taken for identification. This may ignore the baseline information to understand the relationships between the abiotic factors. Therefore, the objective of this study was to determine the effects of the slope position and sampling time on the diversity indices of soil fauna under coconut cultivation planted in the low slope gradient area. The study was conducted in December 2021 at the coconut farm, UiTM Perlis Branch, Malaysia using a Randomized Complete Block Design with four replications. This coconut farm lies on a low slope gradient ranging from 0o to 6o. In total, 96 pitfall traps were installed within the coconut area based on three slope positions (i.e., S1-bottom, S2-middle and S3-top). The soil fauna was collected three times (i.e., T1, T2 and T3) within a month of the study period. The soil fauna specimens were identified up to family level and five of the soil fauna indices (i.e, richness, abundance, Shannon-Wiener diversity index, Simpson’s reciprocal index and evenness index) were calculated. As a result, 1,335 individuals from 10 orders and 15 families were identified in this study. The Formicidae (69.7%) and Scolopendridae (0.1%) groups had the most abundant and lowest number of individual soil fauna found in the coconut farm, respectively. Meanwhile, Termitidae (6.5%), Gryllidae (3.4%), Carabidae (2.8%), Acrididae and Paradioxosomaridae (1.6%) and Alydidae (1.5%) are the most average of individual soil fauna. Results showed that the abundance was significantly highest (41±8.4) at the top position (S3) compared to the other positions and this might be caused by the microclimate factor like moisture and temperature. Meanwhile, the sampling time of T3 shows a significantly highest of richness (7±1.2), the Shannon-Wiener diversity index (1.2±0.3), and Simpson’s reciprocal index (2.5±0.6) and this might be caused by management practices like weed control. Overall, this coconut farm has moderate diversity with high variability of soil fauna during the study.